Primary cilia-associated signalling in squamous cell carcinoma of head and neck region - Putnová, Iveta; Putnová, Barbora Moldovan; Hurník, Pavel; Štembírek, Jan; Buchtová, Marcela; Kolísková, Petra (Frontiers in Oncology, 2024)
Squamous cell carcinoma (SCC) of the head and neck originates from the mucosal lining of the upper aerodigestive tract, including the lip, tongue, nasopharynx, oropharynx, larynx and hypopharynx. In this review, we summarise what is currently known about the potential function of primary cilia in the pathogenesis of this disease. As primary cilia represent a key cellular structure for signal transduction and are related to cell proliferation, an understanding of their role in carcinogenesis is necessary for the design of new treatment approaches. Here, we introduce cilia-related signalling in head and neck squamous cell carcinoma (HNSCC) and its possible association with HNSCC tumorigenesis. From this point of view, PDGF, EGF, Wnt and Hh signalling are discussed as all these pathways were found to be dysregulated in HNSCC. Moreover, we review the clinical potential of small molecules affecting primary cilia signalling to target squamous cell carcinoma of the head and neck area.